Answer:
Explanation:
1) The center lies on the vertical line x = -5 and the the circle is tangent to (touches in one place only) the y-axis. Thus, the radius is 5.
2) Starting with (x - h)^2 + (y - k)^2 = r^2 and comparing this to the given
(x - 4)^2 + (y + 3)^2 = 6^2
we see that h = 4, k = -3 and r = 6. The center is at (4, -3) and the radius is 6.
3) Notice that A and B have the same x-coordinate, x = 15. The center of the circle is thus (15, -2), where that -2 is the halfway point between the two given points in the vertical direction. Arbitrarily choose A(15, 4) as one point on the circle. Then the equation of this circle is
(x - 4)^2 + (y + 3)^2 = r^2 = 6^2, where the 6 is one half of the vertical distance between A(15, 4) and B(15, -8) (which is 12).